Analisis Rasio Likuiditas dan Solvabilitas Sebagai Dasar Penilaian Kinerja Keuangan pada PT JNE Express Timika - Sri Rahayu; Tuti Fitriani (Journal of Financial and Tax, 2023)
This study aims to determine the company's financial performance at PT JNE Express Timika, using liquidity and solvency ratio analysis. The method used in this study is the comparative descriptive method. The data analysis instruments used are: a) measuring the company's liquidity level. b) measure the level of solvency of the company. The results of data analysis show that: a) The ability of PT JNE Express Timika to cover its short-term liabilities seen from the current ratio can be said to be quite good because the company is quite capable of guaranteeing current debt using its current assets, judging from the quick ratio it can be said to be less good due to the lack of availability of company cash in covering its current liabilities, when viewed from the company's cash ratio is quite good because the cash and cash equivalents owned are quite capable To pay off obligations that will mature, while viewed from the cash turn over ratio, it can be said to be not good because the company has not been able to generate income through its net capital. b) The amount of assets of PT JNE Express Timika financed by debt seen from the debt to assest ratio, debt to equity ratio and coverage ratio is very good where the amount of assets and capital of the company financed by debt is very small from year to year and the company's ability to cover its debt from the profits generated is also quite good from year to year